Combining hazard, social vulnerability and resilience to provide a proposal for seismic risk assessment. Issue 9 (1st September 2020) - Azzimonti, Oscar Luigi; Colleoni, Matteo; De Amicis, Mattia; Frigerio, Ivan
Abstract: This research has been produced in the context of the updating of regional and national directives for predicting, mitigating and preventing seismic risk and for implementing regular and emergency local planning policies. Applied to the municipalities of Lombardy, it proposes a range of indicators aimed at describing and analysing the local features that make a place and the populations who live there, or periodically pass through it, more vulnerable and less resilient. More specifically, the study comprises the construction of two indices: a vulnerability index to understand the characteristics of a place that amplify risk, increasing the damage potentially caused by an earthquake in the emergency phase; and a resilience index, which summarises the resources available for reconstruction and the capacity for progressively restoring normality in the long run. The development of the indicators and indices follows a critical review of the American literature, the European debate on risk governance and the recent studies on social vulnerability in Italy. Attention is also devoted to elements usually underestimated in vulnerability research, such as places' transport links and accessibility. Carried out using ecological research and GIS methods and techniques, the study proposes an analytical (social and territorial) and mapping-based interpretation of social vulnerability and resilience in Lombardy.